Seeing What Is Not There : Figuring the Anarchive - Zaayman, Carine, (Literature and Cultural Studies E-Books Online, Collection 2026., 2026)
Any encounter with colonial archives leaves one deeply aware that the voices of the oppressed have been rendered mute. In this book, Zaayman delves into the archives associated with Krotoa and Anne Barnard, two women who lived in the Cape colony. Through them, she identifies the absolute absences that attend all archives, and names them "the Anarchive". This term signals irrecoverability and compels us to turn our attention towards the intangible ways in which the past lives with us in the present, away from the archive. Employing artistic methodologies to instantiate the Anarchive, Zaayman intimates the immense losses brought about by colonialism.